1977
DOI: 10.1093/ajcn/30.2.235
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C, the common cold, and iron absorption

Abstract: A sizable segment of the population was found to be taking large quantities of vitamin C to reduce the number or severity of upper respiratory infections. To determine the affect of this supplementation on iron balance, multiple radioiron absorption tests were performed in 63 male subjects. The increase in iron absorption from a semisynthetic meal was directly proportional to the amount of ascorbic acid added over a range of 25 to 1,000 mg. The ratio of iron absorption with/without ascorbic acid at these two e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
111
0
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(118 citation statements)
references
References 15 publications
3
111
0
2
Order By: Relevance
“…Several studies have shown that progressively increasing the ascorbic acid content in an iron-forti ed food progressively increases fractional iron absorption. [41][42][43][44] The question for the manufacturer is how much ascorbic acid must be added to achieve a meaningful increase in iron absorption.…”
Section: Ascorbic Acid Additionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that progressively increasing the ascorbic acid content in an iron-forti ed food progressively increases fractional iron absorption. [41][42][43][44] The question for the manufacturer is how much ascorbic acid must be added to achieve a meaningful increase in iron absorption.…”
Section: Ascorbic Acid Additionmentioning
confidence: 99%
“…It should be stressed, however, that this might not be suf cient for meals high in phytate or phenolic compounds. An ascorbic acid-to-iron ratio (weight:weight) of approximately 6:1 has been reported to increase iron absorption by 2-to 12-fold in adult women fed infant formula, infant cereal, and enriched maize porridge forti ed with ferrous sulfate or ferric ammonium citrate acid; 45 iron absorption is increased by threefold from a ferrous sulfate-forti ed chocolate drink fed to children; 43 iron absorption is increased by 2.5-fold from a ferric chloride-forti ed liquid formula meal fed to adults; 41 and iron absorption is increased approximately twofold from ferrous sulfateforti ed infant formula fed to infants. 46 However, an ascorbic acid-to-iron ratio (weight:weight) of 10:1 was necessary to approximately double iron absorption by adults from maize porridge 44 and high-phytate bread 42 (both were forti ed with ferrous sulfate).…”
Section: Ascorbic Acid Additionmentioning
confidence: 99%
“…Prior to a trial for correction of iron deficiency anemia by oral iron supple ment, the bioavailability of iron derivatives was tested with FeAC and sodium ferrous citrate. In previous studies, iron absorption was enhanced when given together with vitamin C (20)(21)(22)(23)(24)(25). In the present study , the elevating effect of vitamin C was examined with normal iron-index subjects (n=8; male , aged 26-31, average of 28 years) by measuring their SI levels after administration of the respective iron citrate compound, equivalent to 6 mg iron , with or without 500 mg of vitamin C.…”
mentioning
confidence: 91%
“…Both vegetables are reported to contain similar amounts of polyphenols (B100 mg/100 g wet weight) (Ninfali and Bacchiocca, 2003;Chun et al, 2004), an important class of inhibitors of iron absorption (Hurrell et al, 1999), but may vary in content. Ascorbic acid is a potent enhancer of iron absorption (Cook and Monsen, 1977;Hallberg et al, 1986) and kale has been reported to contain 105 mg/100 g compared to 52 mg/100 g in spinach (Souci et al, 1994). Iron absorption was measured based on the incorporation of stable iron isotope labels into erythrocytes (Kastenmayer et al, 1994;Walczyk et al, 1997).…”
Section: Introductionmentioning
confidence: 99%